Adsorption and dissociation of H2O2 on Cu2O(111) and F, N-doped Cu2O(111) surfaces for potential anti-microbial and anti-pollutant properties - Beronio, Ellaine Rose A.; Santos-Putungan, Alexandra B.; Putungan, Darwin B.; Padama, Allan Abraham B. (Philippine journal of science)
"In this work. we probed the adsorption and dissociation of H2O2 on pristine plus nitrogen-and fluorine-doped Cu2O (111) surfaces via density functional theory to assess their efficacy as anti-microbial and anti-pollutant materials. It is found that H2O2 is chemisorbed on all surfaces with spontaneous dissociation into two OH species. Such dissociative adsorption is a result of charge transfer from the copper atom to H2O2, which activates the cleaving of the O-O bond. Further charge analysis revealed that charge transfer is most active in fluorine-doped Cu2O (111), which makes F-Cu2O (111) the most active surface in H2O2 adsorption and dissociation" - title page.